Avaliação do conhecimento da população Sobre formas de transmissão e medidas Preventivas da toxoplasmose em Mossoró-RN - Rodrigues, Débora Nair Jales (Universidade Federal Rural do Semi-Árido, 2015)
Toxoplasmosis is a cosmopolitan infection caused by the protozoan Toxoplasma gondii, achieving high rates of infection in Brazil and worldwide. The infective forms of the parasite (taquezoítos, bradyzoites and oocysts) that allow humans and other species of animals become infected in several ways, by transplacental form (congenital, from mother to child); handling feces of cats; handling of soil (sand); eating raw or undercooked meat, among other forms. However, infection with Toxoplasma gondii can be mitigated by carrying out preventive measures, such measures are directly related to behavioral and hygienic habits of the population. Thus, starting from pre supposed that the knowledge about the modes of transmission and preventive measures of toxoplasmosis would be precursor to inhibit the increase of infection, the study aimed to assess the population's knowledge about the modes of transmission and preventive measures of toxoplasmosis in Mossoró - RN. Then, a field study was conducted in the municipality, and followed by visits to the Basic Health Units in six districts, with a population of 384 women in the age group classified as reproductive (18-49 years). They were submitted to a questionnaire containing 40 questions, which dealt with the knowledge of transmission and preventive measures of toxoplasmosis. The data obtained from the questionnaires were statistically analyzed with the aid of R program, and use of non-parametric test to compare Fisher Exact women's knowledge about the modes of transmission and their schooling. It was found that most women are unaware of the main frame forms of transmission of toxoplasmosis, this ignorance, had statistical relationship with the education of the respondents. In what refers to preventive measures, most of the population practices without even having knowledge about the ways of transmission. It was concluded that the fact that women practice preventive measures, even knowing the modes of transmission, can is related to lifestyle and custom of the population. It was also observed that most of the women surveyed do not know the IgG test for toxoplasmosis, adding yet, the fact of not having the examination or not knowing respond if at some point would have already done
Evaluation of knowledge of population on forms of transmission And preventive measures in toxoplasmose Mossoró-RN
Keywords: toxoplasmosis, forms of infection, prevention measures; toxoplasmose, formas de contágio, medidas de prevenção; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE